2019
DOI: 10.1002/marc.201800805
|View full text |Cite
|
Sign up to set email alerts
|

Highly Thermally Conductive Polyimide Composites via Constructing 3D Networks

Abstract: Easy and high efficient methods are in great demand to obtain polyimide (PI) composites with high thermal conductivity in the electronic packaging field. In this work, PI/boron nitride (BN) composites with high thermal conductivity are easily fabricated. Tightly connected and well‐arranged BN platelets construct effective 3D thermally conductive networks in the PI matrix upon hot pressing, after BN platelets are coated on the surface of PI granules by the help of a kind of PI adhesive. The thermal conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…The distinguished comprehensive performance of these composites is conductive for pervasive application in marine, aerospace, radiation shielding, and electronic fields [1][2][3][4][5]. The common resin matrix for advanced composites are epoxy [6,7], polyimide [8][9][10], polyetheretherketone [11,12], and the best heat-resistant resin during last four decades-phthalonitrile [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The distinguished comprehensive performance of these composites is conductive for pervasive application in marine, aerospace, radiation shielding, and electronic fields [1][2][3][4][5]. The common resin matrix for advanced composites are epoxy [6,7], polyimide [8][9][10], polyetheretherketone [11,12], and the best heat-resistant resin during last four decades-phthalonitrile [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Common thermally used conductive fillers are metals (Ag [8] and Cu [9]), carbon-based (graphene [10], carbon nanotubes [11]), and ceramics (BN [12], Al 2 O 3 [13], and AlN [14,15]). Metal fillers and carbon-based fillers also increase electrical conductivity while improving mechanical and thermal properties; however, they are disadvantageous for Insulation properties of thermal interface materials.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, poor interface combination between a thermal conductivity filler and polymer matrix leads to poor dispersion of the filler. These all cause strong phonon scattering and reduce phonon transmission efficiency, and then lead to the poor thermal conductivity of the interface [12,18,20,27,28]. It is reported that surface modification and functionalization of the filler can improve compatibility with the polymer matrix [29,30].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the rapid development of highperformance microelectronic equipment and energy harvesting devices, the demand for heat sinks in industrial and electronic elds has dramatically increased. 1,2 However, the thermal conductivity of common polymers is quite low and ranges from 0.1 W m À1 K À1 to 0.3 W m À1 K À1 . Hence, their applications are severely limited in industrial and electronic elds due to heat accumulation.…”
Section: Introductionmentioning
confidence: 99%